Pencegahan primer pada anak yang berisiko karies tinggi (Primary prevention in children with high caries risk) - Ami Angela (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Oral and dental health has got improvement tremendously over the last century but the prevalence of dental caries in children has remained a significant clinical problem. Caries risk varies between individuals according to each subject’s balance between factors exposing to and protecting from caries attack. It is important to assess the risk of caries for all patients on a routine basis. Caries risk is divided into three levels: high, moderate, and low. Thereby, the dental professional is better to make a specific prevention and treatment recommendations to reduce a child risk and improve overall oral health. The goal of caries-risk assessment and preventive treatment is to eliminate caries or at least to reduce the high-caries occurrence down to the level of the remaining part of the age group. Preventive treatment is divided into three parts: primary, secondary, and tertiary prevention. This paper describes the primary prevention in children with high caries risk by behavior modification and tooth protection. Behavior modification is about dental health education, oral hygiene, diet and sugar consumption, sugar-free chewing gum and sugar-free medicines. Tooth protection is about sealant, usage of flouride and chlorhexidine.